Chronic and intermittent administration of systemic nitroglycerin in the rat induces an increase in the gene expression of CGRP in central areas: potential contribution to pain processing - Rosaria Greco; Chiara Demartini; Anna Maria Zanaboni; Cristina Tassorelli (The Journal of Headache and Pain, 2018)
Abstract Background Calcitonin gene related peptide (CGRP) is a key neuropeptide involved in the activation of the trigeminovascular system and it is likely related to migraine chronification. Here, we investigated the role of CGRP in an animal model that mimics the chronic migraine condition via repeated and intermittent nitroglycerin (NTG) administration. We also evaluated the modulatory effect of topiramate on this experimental paradigm. Male Sprague-Dawley rats were injected with NTG (5 mg/kg, i.p.) or vehicle, every 2 days over a 9-day period (5 total injections). A group of animals was injected with topiramate (30 mg/kg, i.p.) or saline every day for 9 days. Twenty-four hours after the last administration of NTG or vehicle, animals underwent tail flick test and orofacial Von Frey test. Rats were subsequently sacrificed to evaluate c-Fos and CGRP gene expression in medulla-pons region, cervical spinal cord and trigeminal ganglia. Results NTG administration induced spinal hyperalgesia and orofacial allodynia, together with a significant increase in the expression of CGRP and c-Fos genes in trigeminal ganglia and central areas. Topiramate treatment prevented NTG-induced changes by reversing NTG-induced hyperalgesia and allodynia, and inhibiting CGRP and c-Fos gene expression in all areas evaluated. Conclusions These findings point to the role of CGRP in the processes underlying migraine chronification and suggest a possible interaction with gamma-aminobutyrate (GABA) and glutamate transmission to induce/maintain central sensitization and to contribute to the dysregulation of descending pain system involved in chronic migraine.